Polyurethane polishing material and preparation method thereof
By adding nano cerium oxide and nanographene oxide to the polyurethane polishing material, combined with the use of polytetrafluoroethylene resin and calcium oxide, the problem of poor hydrolysis stability of the polyurethane polishing pad is solved, achieving efficient and stable polishing effect and extension The effect of service life.
Patent Information
- Application Number
- CN202410494496.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-24
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-04-24
AI Technical Summary
During the use of existing polyurethane polishing pads, due to poor hydrolysis stability, the polishing efficiency and unstable properties are difficult to meet the needs of the chemical mechanical polishing field.
By adding nano cerium oxide and nanographene oxide as nanoadditives to the polyurethane polishing material and dispersing uniformly in the thermoplastic polyurethane resin, combining the use of polytetrafluoroethylene resin and calcium oxide, polyurethane polishing with high hydrolysis stability was prepared. Material.
It significantly improves the hydrolytic stability of polyurethane polishing materials, enhances the stability and efficiency during the polishing process, and extends the service life of the polishing pad.
Smart Images

Figure BDA0004806498530000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polishing materials, and more specifically, relates to a polyurethane polishing material and a preparation method thereof. Background Art
[0002] Polyurethane (PU) polishing materials are widely used in chemical mechanical polishing (CMP) processes due to their excellent mechanical, physical and chemical properties. However, the hydrolysis stability of polyurethane materials is one of the technical issues that need to be focused on and improved during their application.
[0003] The reason why the hydrolysis reaction occurs is mainly because the polyurethane elastomer will degrade when it comes into contact with water or moisture, resulting in a decrease in physical and mechanical properties. The polyurethane molecular chain contains ester groups, carbamate groups and urea groups. The presence of these groups limits its water resistance and makes it prone to hydrolysis.
[0004] The hydrolytic stability of polyurethane is affected by many factors, including the chemical structure of polyurethane (such as the type and ratio of soft and hard segments), environmental conditions (such as temperature, pH and humidity), and the physical state of the polyurethane material (such as density and porosity).
[0005] Polyurethane polishing pads with good hydrolytic stability have important practical application value in the field of chemical mechanical polishing, which can improve polishing efficiency and polishing quality, and prolong the service life of the polishing pad. Therefore, how to provide a polyurethane polishing material with good hydrolytic stability is one of the technical problems that those skilled in the art need to solve. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the problem that the existing polyurethane polishing pads are prone to poor polishing efficiency and unstable properties during the polishing process due to poor hydrolysis stability during use, and provide a polyurethane polishing material and a preparation method thereof.
[0007] The purpose of the present invention is to provide a polyurethane polishing material.
[0008] Another object of the present invention is to provide a method for preparing a polyurethane polishing material.
[0009] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0010] A polyurethane polishing material, comprising thermoplastic polyurethane resin and nano additives;
[0011] The nano additives include nano cerium oxide and nano graphene oxide;
[0012] Wherein, the nano graphene oxide comprises stacked graphene sheets, and the nano cerium oxide is at least partially dispersed between the graphene sheets; and at least a portion of the nano cerium oxide is directly dispersed in the thermoplastic polyurethane resin;
[0013] The mass ratio of the nano-cerium oxide to the nano-graphene oxide is 1:1.8-1:2.2;
[0014] In the thermoplastic polyurethane resin, the amount of the nano additive is 10-12.5% of the mass of the thermoplastic polyurethane resin.
[0015] Furthermore, sodium dodecylbenzene sulfonate is also included between the graphene sheets.
[0016] Furthermore, the ratio of D50 of the nano-cerium oxide to the nano-graphene oxide is 1:8-1:10; and the D50 of the nano-cerium oxide is 10-15 nm.
[0017] Furthermore, the polyurethane polishing material further comprises polytetrafluoroethylene resin accounting for 10-25% of the mass of the thermoplastic polyurethane resin.
[0018] Furthermore, the polyurethane polishing material also includes calcium oxide and calcium hydroxide.
[0019] A method for preparing a polyurethane polishing material, the specific preparation steps comprising:
[0020] Preparation of nano additives:
[0021] The nano-graphene oxide is ultrasonically dispersed in a solvent at an ultrasonic frequency of 150-160kHz, and then nano-cerium oxide is added, and the ultrasonic dispersion is continued at a frequency of 50-60kHz, followed by suction filtration and drying to obtain a nano-additive;
[0022] Preparation of polishing materials:
[0023] The nano additive and the thermoplastic polyurethane resin are uniformly mixed, heated and mixed at 200-220° C., hot-pressed in a mold, cold-pressed, and demolded to obtain a polyurethane polishing material.
[0024] Furthermore, the preparation of the nano additive also includes:
[0025] The nano graphene oxide is ultrasonically dispersed in a solvent at an ultrasonic frequency of 150-160kHz, and then nano cerium oxide and sodium dodecylbenzene sulfonate in an amount of 3-5% by mass of the nano graphene oxide are added, and the nano additive is further ultrasonically dispersed at a frequency of 50-60kHz, and then filtered and dried to obtain the nano additive.
[0026] Furthermore, the preparation of the polishing material also includes:
[0027] After the nano additive and the thermoplastic polyurethane resin are uniformly mixed, 10-25% of the mass of the thermoplastic polyurethane resin is added with polytetrafluoroethylene resin, heated and mixed at 200-220° C., hot-pressed in a mold, cold-pressed, and demolded to obtain a polyurethane polishing material.
[0028] Furthermore, the preparation of the polishing material also includes:
[0029] After the nano additive and the thermoplastic polyurethane resin are uniformly mixed, calcium oxide is added, and the mixture is heated and mixed at 200-220° C., and then hot-pressed in a mold, cold-pressed, and demolded to obtain a polyurethane polishing material; wherein part of the calcium oxide is converted into calcium hydroxide due to water absorption during the processing.
[0030] Furthermore, the preparation of the polishing material also includes:
[0031] After the nano additive and the thermoplastic polyurethane resin are uniformly mixed, calcium oxide and 10-25% of the mass of polytetrafluoroethylene resin of the thermoplastic polyurethane resin are added, and the mixture is heated and mixed for 15-20 minutes at a temperature of 200-220° C. and a rotation speed of 50-60 r / min in a torque rheometer. After the mixing is completed, the mixture is dried in an oven at 65-75° C. for 10-12 hours, and then hot-pressed for 3-5 minutes in a mold at a temperature of 200-210° C. and a pressure of 8-10 MPa, and then cold-pressed for 2-4 minutes and demolded to obtain a polyurethane polishing material.
[0032] Beneficial technical effects:
[0033] (1) The present invention disperses nano-cerium oxide between graphene sheets of nano-graphene oxide in advance, thereby effectively avoiding agglomeration of nano-cerium oxide when added to thermoplastic polyurethane resin; at the same time, due to the presence of nano-cerium oxide, it can effectively widen the interlayer spacing of the graphene sheets of nano-graphene oxide. On the one hand, thanks to the stable and uniform dispersion of the nano-additives in the thermoplastic polyurethane, the nano-additives can be evenly dispersed in the soft segments of the thermoplastic polyurethane molecular chain segments, increasing the distance between the hard segments of the thermoplastic polyurethane molecular chain, and increasing the orderliness of the arrangement, thereby effectively improving the stability of the material during the polishing process; on the other hand, the improvement of the dispersion uniformity allows relatively more nano-additives to be added to the system, so that the product has a relatively higher solid content, thereby improving the hydrolysis stability of the product; in addition, as the spacing between graphene sheets widens, during the product processing, the increase in solid content does not significantly increase the viscosity of the processing system, because the graphene sheets after the widened interlayer spacing can act as a lubricant, and secondly, during the polishing process, the layers are more likely to slip in the presence of cerium oxide, thereby effectively avoiding the occurrence of hydrolysis reactions due to overheating of the material during the polishing process;
[0034] (2) The present invention further adds polytetrafluoroethylene resin to the thermoplastic polyurethane resin. Since the polytetrafluoroethylene resin has a very low surface energy, its addition can significantly reduce the contact between water molecules and polar groups in the polyurethane chain segments, thereby reducing the possibility of hydrolysis reaction. By adjusting the amount of polytetrafluoroethylene resin added, if the amount added reaches 10%, the micropores and defects in the thermoplastic polyurethane resin caused by the introduction of nano-additives can be effectively reduced; however, if the amount added is too high, when it is higher than 25%, it will affect the stable dispersion of the nano-additives in the thermoplastic polyurethane. DETAILED DESCRIPTION
[0035] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0036] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0037] Example 1
[0038] Preparation of nano additives:
[0039] After mixing nano graphene oxide and solvent deionized water in a mass ratio of 1:10, the mixture was subjected to constant temperature ultrasonic dispersion for 2 hours at a temperature of 40°C and an ultrasonic frequency of 150kHz, and then nano cerium oxide and sodium dodecylbenzene sulfonate in an amount of 3% by mass of the nano graphene oxide were added, and the mixture was further subjected to constant temperature ultrasonic dispersion for 60 minutes at a temperature of 40°C and an ultrasonic frequency of 50kHz, and then the mixture was transferred to a Buchner funnel for suction filtration, and the filter cake was collected and transferred to an oven for drying at a temperature of 100°C to constant weight to obtain a nano additive;
[0040] Firstly, a relatively high ultrasonic frequency and a relatively long time are used to make the graphene oxide with a sheet structure peel off in water to form a single sheet structure, and then sodium dodecylbenzene sulfonate is used to assist the dispersion of nano-cerium oxide and the adsorption on the surface of the single sheet graphene oxide. During the filtration process, the graphene oxide sheet structure is re-stacked, and the adsorbed nano-cerium oxide is embedded in its interlayer structure during the stacking process, while part of the nano-cerium oxide is not embedded due to its dispersion in the solution, and is only dispersed by ordinary physical mixing;
[0041] The ratio of D50 of the nano-cerium oxide to the nano-graphene oxide is 1:8; and the D50 of the nano-cerium oxide is 10 nm;
[0042] The mass ratio of the nano-cerium oxide to the nano-graphene oxide is 1:1.8;
[0043] Preparation of polishing materials:
[0044] The nano additive and the thermoplastic polyurethane resin are first dried in an oven at a temperature of 90° C. for 2 hours, and then stirred and mixed with a stirrer at a speed of 300 r / min for 20 minutes, and then calcium oxide (2% by weight of the thermoplastic polyurethane resin) and polytetrafluoroethylene resin (10% by weight of the thermoplastic polyurethane resin) are added, and heated and mixed for 15 minutes in a torque rheometer at a temperature of 200° C. and a speed of 50 r / min. After the mixing is completed, the mixture is dried in an oven at 65° C. for 10 hours, and then hot-pressed in a mold at a temperature of 200° C. and a pressure of 8 MPa for 3 minutes, and then cold-pressed for 2 minutes and demolded to obtain a polyurethane polishing material;
[0045] In the thermoplastic polyurethane resin, the amount of the nano additive is 10% of the mass of the thermoplastic polyurethane resin;
[0046] Since part of the nano-cerium oxide is not embedded in the graphene oxide layer, it is directly dispersed in the resin system during the resin mixing process.
[0047] Example 2
[0048] Preparation of nano additives:
[0049] After mixing nano graphene oxide and solvent deionized water in a mass ratio of 1:10, the mixture was subjected to constant temperature ultrasonic dispersion for 2.5 hours at a temperature of 50°C and an ultrasonic frequency of 150kHz, and then nano cerium oxide and sodium dodecylbenzene sulfonate in an amount of 4% by mass of the nano graphene oxide were added, and the mixture was further subjected to constant temperature ultrasonic dispersion for 80 minutes at a temperature of 50°C and an ultrasonic frequency of 55kHz, and then the mixture was transferred to a Buchner funnel for suction filtration, and the filter cake was collected and transferred to an oven for drying at a temperature of 105°C to constant weight to obtain a nano additive;
[0050] Firstly, a relatively high ultrasonic frequency and a relatively long time are used to make the graphene oxide with a sheet structure peel off in water to form a single sheet structure, and then sodium dodecylbenzene sulfonate is used to assist the dispersion of nano-cerium oxide and the adsorption on the surface of the single sheet graphene oxide. During the filtration process, the graphene oxide sheet structure is re-stacked, and the adsorbed nano-cerium oxide is embedded in its interlayer structure during the stacking process, while part of the nano-cerium oxide is not embedded due to its dispersion in the solution, and is only dispersed by ordinary physical mixing;
[0051] The ratio of D50 of the nano-cerium oxide to the nano-graphene oxide is 1:9; and the D50 of the nano-cerium oxide is 12 nm;
[0052] The mass ratio of the nano-cerium oxide to the nano-graphene oxide is 1:2;
[0053] Preparation of polishing materials:
[0054] The nano additive and the thermoplastic polyurethane resin are first dried in an oven at a temperature of 95° C. for 3 hours, and then stirred and mixed with a stirrer at a speed of 350 r / min for 30 minutes. Then, calcium oxide (3% by weight of the thermoplastic polyurethane resin) and polytetrafluoroethylene resin (20% by weight of the thermoplastic polyurethane resin) are added, and heated and mixed for 18 minutes at a temperature of 210° C. and a speed of 55 r / min in a torque rheometer. After the mixing is completed, the mixture is dried in an oven at 70° C. for 11 hours, and then hot-pressed in a mold at a temperature of 205° C. and a pressure of 9 MPa for 4 minutes, and then cold-pressed for 3 minutes and demolded to obtain a polyurethane polishing material;
[0055] In the thermoplastic polyurethane resin, the amount of the nano additive is 11.5% of the mass of the thermoplastic polyurethane resin;
[0056] Since part of the nano-cerium oxide is not embedded in the graphene oxide layer, it is directly dispersed in the resin system during the resin mixing process.
[0057] Example 3
[0058] Preparation of nano additives:
[0059] After mixing nano graphene oxide and solvent deionized water in a mass ratio of 1:10, the mixture was subjected to constant temperature ultrasonic dispersion for 3 hours at a temperature of 60°C and an ultrasonic frequency of 160kHz, and then nano cerium oxide and sodium dodecylbenzene sulfonate in an amount of 5% by mass of the nano graphene oxide were added, and the mixture was further subjected to constant temperature ultrasonic dispersion for 100 minutes at a temperature of 60°C and an ultrasonic frequency of 60kHz, and then the mixture was transferred to a Buchner funnel for suction filtration, and the filter cake was collected and transferred to an oven for drying at a temperature of 110°C to constant weight to obtain a nano additive;
[0060] Firstly, a relatively high ultrasonic frequency and a relatively long time are used to make the graphene oxide with a sheet structure peel off in water to form a single sheet structure, and then sodium dodecylbenzene sulfonate is used to assist the dispersion of nano-cerium oxide and the adsorption on the surface of the single sheet graphene oxide. During the filtration process, the graphene oxide sheet structure is re-stacked, and the adsorbed nano-cerium oxide is embedded in its interlayer structure during the stacking process, while part of the nano-cerium oxide is not embedded due to its dispersion in the solution, and is only dispersed by ordinary physical mixing;
[0061] The ratio of D50 of the nano-cerium oxide to the nano-graphene oxide is 1:10; and the D50 of the nano-cerium oxide is 15 nm;
[0062] The mass ratio of the nano-cerium oxide to the nano-graphene oxide is 1:2.2;
[0063] Preparation of polishing materials:
[0064] The nano additive and the thermoplastic polyurethane resin are first dried in an oven at a temperature of 100° C. for 4 hours, and then stirred and mixed with a stirrer at a speed of 400 r / min for 40 minutes, and then calcium oxide (4% by weight of the thermoplastic polyurethane resin) and polytetrafluoroethylene resin (25% by weight of the thermoplastic polyurethane resin) are added, and heated and mixed for 20 minutes at a temperature of 220° C. and a speed of 60 r / min in a torque rheometer. After the mixing is completed, the mixture is dried in an oven at 75° C. for 12 hours, and then hot-pressed in a mold at a temperature of 210° C. and a pressure of 10 MPa for 5 minutes, and then cold-pressed for 4 minutes and demolded to obtain a polyurethane polishing material;
[0065] In the thermoplastic polyurethane resin, the amount of the nano additive is 12.5% of the mass of the thermoplastic polyurethane resin;
[0066] Since part of the nano-cerium oxide is not embedded in the graphene oxide layer, it is directly dispersed in the resin system during the resin mixing process.
[0067] Example 4
[0068] The difference between this embodiment and embodiment 1 is that sodium dodecylbenzene sulfonate is not added, and the other conditions remain unchanged. Compared with embodiment 1, due to the lack of sodium dodecylbenzene sulfonate, the amount of nano-cerium oxide embedded in the graphene oxide layer is reduced.
[0069] Example 5
[0070] The difference between this embodiment and embodiment 1 is that no polytetrafluoroethylene resin is added, and other conditions remain unchanged.
[0071] Example 6
[0072] The present embodiment differs from the embodiment 1 in that polypropylene of equal mass is used to replace the polytetrafluoroethylene resin, and the other conditions remain unchanged.
[0073] Example 7
[0074] The difference between this embodiment and embodiment 1 is that the added amount of polytetrafluoroethylene resin is 8% of the mass of the thermoplastic polyurethane resin, and the other conditions remain unchanged.
[0075] Example 8
[0076] The difference between this embodiment and embodiment 1 is that the added amount of polytetrafluoroethylene resin is 27% of the mass of the thermoplastic polyurethane resin, and the other conditions remain unchanged.
[0077] Example 9
[0078] Compared with Example 1, this embodiment differs in that calcium oxide is not added, and other conditions remain unchanged.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that an equal mass of amorphous carbon is used to replace nano-graphene oxide, and other conditions remain unchanged.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 1 is that no nano-graphene oxide is added, and the other conditions remain unchanged.
[0083] The performance tests were performed on the products obtained in Examples 1-9 and Comparative Examples 1-2. The specific test methods and test results are as follows:
[0084] Friction coefficient and material removal rate test:
[0085] A copper sheet with a diameter of 60 mm and a thickness of 3 mm is used as a polished sample, wherein the copper sheet is a pure copper sheet;
[0086] The product obtained in the embodiment or comparative example was made into a polishing pad with a diameter of 60 mm and a thickness of 3.5 mm. The polishing was continued for 25 min at a rotation speed of 50 r / min. The mass of the copper sheet before and after polishing was tested. The material removal rate after polishing was X = (mass of the copper sheet before polishing - mass of the copper sheet after polishing) / (10 6 ·ρ·π·R 2 ·t); where mass unit is g, ρ is the density of the copper sheet = 8.9×10 -3 g / mm 3 ; R is the diameter of the copper sheet, mm; t is the polishing time, min;
[0087] A vertical friction and wear testing machine was used to examine the friction coefficient of the product at different time periods.
[0088] Detailed test results are shown in Table 1;
[0089] Table 1: Product performance test results
[0090]
[0091] It can be seen from the test results in Table 1 that the product obtained by the present invention has a beneficial polishing effect, and the friction coefficient remains relatively stable during a long period of friction, which indirectly confirms that the properties of the material remain overall stable during use.
[0092] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A polyurethane polishing material, characterized in that: Including thermoplastic polyurethane resin, nano additives; The nano additives include nano cerium oxide and nano graphene oxide; Wherein, the nano graphene oxide comprises stacked graphene sheets, and the nano cerium oxide is at least partially dispersed between the graphene sheets; and at least a portion of the nano cerium oxide is directly dispersed in the thermoplastic polyurethane resin; The mass ratio of the nano-cerium oxide to the nano-graphene oxide is 1:1.8-1:2.2; In the thermoplastic polyurethane resin, the amount of the nano additive is 10-12.5% of the mass of the thermoplastic polyurethane resin; The polyurethane polishing material further includes polytetrafluoroethylene resin in an amount of 10-25% by mass of the thermoplastic polyurethane resin; Sodium dodecylbenzene sulfonate is also included between the graphene sheets; The ratio of D50 of the nano-cerium oxide to the nano-graphene oxide is 1:8-1:10; and the D50 of the nano-cerium oxide is 10-15 nm; The polyurethane polishing material also includes calcium oxide and calcium hydroxide.
2. A method for preparing the polyurethane polishing material according to claim 1, characterized in that: The specific preparation steps include: Preparation of nano additives: The nano-graphene oxide is ultrasonically dispersed in a solvent at an ultrasonic frequency of 150-160kHz, and then nano-cerium oxide and sodium dodecylbenzene sulfonate in an amount of 3-5% by mass of the nano-graphene oxide are added, and the nano-graphene oxide is ultrasonically dispersed at a frequency of 50-60kHz, and then filtered and dried to obtain a nano-additive; Preparation of polishing materials: After the nano additive and the thermoplastic polyurethane resin are uniformly mixed, calcium oxide and 10-25% of the mass of the thermoplastic polyurethane resin of polytetrafluoroethylene resin are added, and the mixture is heated and mixed at 200-220° C., and then hot-pressed in a mold, cold-pressed, and demolded to obtain a polyurethane polishing material; Part of the calcium oxide is converted into calcium hydroxide due to water absorption during processing.
3. The method for preparing a polyurethane polishing material according to claim 2, characterized in that: The preparation of the polishing material also includes: After the nano additive and the thermoplastic polyurethane resin are uniformly mixed, calcium oxide and 10-25% of the mass of the polytetrafluoroethylene resin of the thermoplastic polyurethane resin are added, and the mixture is heated and mixed for 15-20 minutes at a temperature of 200-220° C. and a rotation speed of 50-60 r / min in a torque rheometer. After the mixing is completed, the mixture is dried in an oven at 65-75° C. for 10-12 hours, and then hot-pressed for 3-5 minutes in a mold at a temperature of 200-210° C. and a pressure of 8-10 MPa, and then cold-pressed for 2-4 minutes and demolded to obtain a polyurethane polishing material.
Citation Information
Patent Citations
Polyurethane sponge composite polishing disk
CN110003426A
Nano-modified thermoplastic polyurethane elastomer polishing material and preparation method thereof
CN112094493A
Composite material for polishing optical parts and preparation method
CN114196327A